Swift Trust in Ad Hoc Teams: A Cognitive Task Analysis of Intelligence Operators in Multi-Domain Command and Control Contexts. (September 2020) - Capiola, August; Baxter, Holly C.; Pfahler, Marc D.; Calhoun, Christopher S.; Bobko, Philip
Trust is important for establishing successful relationships and performance outcomes. In some contexts, however, rich information such as knowledge of and experience with a teammate is not available to inform one's trust. Yet, parties in these contexts are expected to work together toward common goals for a relatively brief and finite period of time. This research investigated the antecedents to quickly-formed trust (often referred to as swift trust) in fast-paced, time-constrained contexts. We conducted a cognitive task analysis (CTA) based on 11 structured interviews of subject-matter experts (SMEs) in Intelligence (Intel)—a heterogeneous job category comprising distributed and co-located personnel within multi-domain command and control (MDC2) environments. Eight antecedents to swift trust emerged from these interviews (i.e., ability, integrity, benevolence, communication, mission-focus, self-awareness, shared perspectives/experiences, and calm), with further analysis implying that swift trust is a relevant and emergent state in MDC2 that facilitates reliance. These findings offer implications for teams operating in high-risk distributed contexts and should be expanded through basic experimental investigations as well as applied initiatives.